Critical differences in early-stage oxidation of Ni-Cr and Ni-Cr-Mo alloys - Keithen G. Orson; Devin Jessup; Zachary D. Harris; Jerzy T. Sadowski; Petra Reinke (npj Materials Degradation)
Abstract The early-stage oxidation of Ni-22Cr-6Mo (wt%) is studied for low O2 exposure (0-60 Langmuir) in-situ with ultra-high-vacuum synchrotron-based X-ray photoemission electron microscopy (XPEEM) and X-ray photoelectron spectroscopy (XPS). X-ray absorption spectroscopic (XAS) hyperspectral and time-resolved XPEEM images delivers chemical, time resolved, and structural information about oxide growth. Oxide distribution in the XAS hyperspectral images is quantified with cosine similarity. In contrast to what has been observed for binary Ni-Cr, the oxide of the ternary Ni-Cr-Mo grows in a layer-by-layer growth mode for all five grain orientations studied. The oxide is exclusively Cr2O3 in the corundum structure with a (0001) termination with small admixtures of Mo-oxides predominantly as Mo(IV). Mechanisms for the role of Mo in changing the oxide growth mode are discussed.